Development and validation of the scale of knowledge, comfort and attitudes of physiotherapy students towards human sexuality (SKCAPS) - Priscilla Geraldine Wittkopf; Fernando Luiz Cardoso; Fabiana Flores Sperandio
Introduction Recent studies with Physiotherapy students pointed out for attitudes and conflicting perceptions on their learning process during the phase that precedes the clinical practice. One of those aspects is the human sexuality that appears in the close physical contact that demands Physiotherapists professional practices. Objective To build up the first educational/research instrument that evaluates the knowledge, the comfort and the attitudes of Physiotherapy undergraduate students (SKCAPS). Materials and methods From the literature we extracted three dimensions: knowledge, comfort and attitudes. Initially 50 items were created distributed in the three dimensions that went under the content evaluation, 47 items survived from this process and integrate the first version of SKCAPS. In empiric terms the intern coherence and the reliability of the instrument were tested in 248 students. Results The exploratory factorial analysis carried 37 items in 4 factors that explain 68% of the total variance of the answers of the subjects and that confirmed the proposed dimensions. The dimension comfort became separated in comfort and discomfort. The SKCAPS presented good reliability in terms of intern consistence alpha 0.861. Finally, the instrument was administered to 30 Physiotherapy students for evaluation of clarity following the exclusion of two items that resulted in averages below 8.5. Conclusions With the aim of improve the teaching/learning process, we propose the SKCAPS as the first worth and reliable instrument to evaluate the knowledge, the comfort, the discomfort and the attitudes regard of human sexuality among Physiotherapy students.